Knowledge Capture in Agile Organizations: Methods and Strategies for Enhancing Effective and Efficient Process - Pratiwi, Maharani Eka; Ramadhan, Yudistira; Sensuse, Dana Indra; Lusa, Sofian; Safitri, Nadya; Elisabeth, Damayanti (Universitas Dharma Wacana, 2024)
The competitive landscape of modern organizations relies on efficient knowledge utilization and management, underscoring the crucial role of knowledge capture in effective Knowledge Management (KM). This study explores the relationship between knowledge capture, organizational agility, and employee proficiency within KM, pinpointing critical gaps in understanding the optimal utilization of knowledge capture methods within agile-based setups. By addressing these gaps, the study aims to identify effective knowledge capture methods and propose strategies for their seamless integration into agile organizations. The research investigates five hypotheses, affirming the positive impacts of expert interviews, focus groups, interviews, surveys, and questionnaires on the efficiency and effectiveness of knowledge capture processes in agile contexts. Utilizing a mixed-method approach, this study evaluates qualitative and quantitative data derived from interviews and questionnaires. The results highlight the importance of various knowledge capture methods in augmenting the efficiency and efficacy of the knowledge capture process. Additionally, the study outlines implementation strategies customized for each method's application within agile-based organizations. The objective of this research is to provide practical solutions that narrow the disparity between the potential of knowledge capture and the particular needs of agile setups.